URM1-Mediated Ubiquitin-Like Modification Is Required for Oxidative Stress Adaptation During Infection of the Rice Blast Fungus - Wang, Luyang; Cai, Xuan; Xing, Junjie; Liu, Caiyun; Hendy, Ahmed; Chen, Xiao-Lin (Frontiers in Microbiology, 2019)
Ubiquitin is a small modifier protein which is usually conjugated to substrate proteins for degradation. Recent years, a number of ubiquitin-like proteins have been identified, however, their roles in eukaryotes are largely unknown. Here, we describe a ubiquitin-like protein URM1, and found it plays important roles in development and infection process of the rice blast fungus, Magnaporthe oryzae. Targeted deletion of URM1 in M. oryzae resulted in slight reduction in vegetative growth and significant decrease in conidiation. More importantly, the Δurm1 mutant also showed evident reduction in virulence to host plants. Infection process observation demonstrated that the mutant was arrested in invasive growth, and resulted in accumulation of massive host reactive oxygen species (ROS). Further, we found the Δurm1 mutant was sensitive to the cell wall disturbing reagents, thiol oxidizing agent diamide and rapamycin. We also showed that URM1-mediated modification was responsive to oxidative stresses, and the thioredoxin peroxidase Ahp1 was one of the important urmylation targets. These results suggested that URM1-mediated urmylation plays important roles in detoxification of host oxidative stress to facilitate invasive growth in M. oryzae.